Numerical appraisal of the unsteady Casson fluid flow through Finite Element Method (FEM) - Khader, M. M.; İnç, Mustafa; Akgul, A. (Sharif Univ Technology, 2023)
The current study proposes an efficient numerical method to evaluate the effects of the variable heat flux, viscous dissipation, and slip velocity on the viscous Casson Heat Transfer (CHT), considering the unsteady stretching sheet that took into account the effect of heat generation or absorption. In this respect, Finite Element Method (FEM) was employed to solve the resulting ODEs that described the problem. The effects of the factors governing the HT such as unsteadiness parameter, slip velocity parameter, Casson parameter, local Eckert number, heat generation parameter, and Prandtl number were studied. In addition, the local skin friction coefficient and local Nusselt number on the stretching sheet were also computed. Finally, the obtained solutions confirmed that the proposed procedure could be an easy and efficient tool for finding a solution to such fluid models. (c) 2023 Sharif University of Technology. All rights reserved.
Keywords: Variable heat flux; Slip effect; Viscous dissipation; Heat generation; FEM